2005
DOI: 10.1172/jci200523661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epstein-Barr virus proteins as putative targets of the immune response in multiple sclerosis

Abstract: MS is a chronic inflammatory and demyelinating disease of the CNS with as yet unknown etiology. A hallmark of this disease is the occurrence of oligoclonal IgG antibodies in the cerebrospinal fluid (CSF). To assess the specificity of these antibodies, we screened protein expression arrays containing 37,000 tagged proteins. The 2 most frequent MS-specific reactivities were further mapped to identify the underlying high-affinity epitopes. In both cases, we identified peptide sequences derived from EBV proteins e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
4
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(113 citation statements)
references
References 48 publications
(16 reference statements)
6
97
4
6
Order By: Relevance
“…(Hollsberg et al 2003;Holmoy et al 2004;Lang et al 2002). Consistent with this hypothesis are the presence of immune responses in the CSF of MS patients to two EBV peptides, including EBNA-1 (Cepok et al 2005), the increased frequency and broadened specificity in MS of CD 4+ T cells recognizing EBNA 1, (Lunemann et al 2006) and the report of EBNA-1-pecific cell lines from MS patients crossreacting with myelin antigens (Lunemann et al 2008). Results of the investigations of EBV-specific cytotoxic T cells in MS have been somewhat inconsistent.…”
Section: Bmentioning
confidence: 98%
“…(Hollsberg et al 2003;Holmoy et al 2004;Lang et al 2002). Consistent with this hypothesis are the presence of immune responses in the CSF of MS patients to two EBV peptides, including EBNA-1 (Cepok et al 2005), the increased frequency and broadened specificity in MS of CD 4+ T cells recognizing EBNA 1, (Lunemann et al 2006) and the report of EBNA-1-pecific cell lines from MS patients crossreacting with myelin antigens (Lunemann et al 2008). Results of the investigations of EBV-specific cytotoxic T cells in MS have been somewhat inconsistent.…”
Section: Bmentioning
confidence: 98%
“…Studies of samples from RRMS patients have shown that a significant proportion are positive for EBV EA antigens, suggesting an active viral infection [11]. Similarities between certain epitopes of the EBV EBNA-1 protein and MOBP provides a possible mechanism whereby EBV infection can initiate demyelination [10,21] and recently EBV latent proteins have been identified as targets of oligoclonal bands in MS CSF [12]. Cumulatively, the evidence for EBV involvement in MS is appealing, and we determined to use our post mortem brain samples to look for further evidence as most of the previous studies have been done on PBMCs or CSFs.…”
mentioning
confidence: 99%
“…However, earlier (Serafini et al, 2007) and subsequent studies (Peferoen et al, 2010;Willis et al, 2009) could not reproduce the findings of Serafini et al Whether homing of EBVinfected B cells into the CNS is a primary event remains pure speculation (Serafini et al, 2007). Nevertheless, an involvement of EBV in MS pathogenesis is supported by other investigations (Franciotta et al, 2008): Intrathecal antibodies were found to be specific for EBV proteins (Cepok et al, 2005). Corresponding with previous association studies (Lublin and Reingold, 1996), recent investigations found that increased antibody responses to the EBV protein EBNA1 correlate with MRI severity and predict the conversion of clinically isolated syndrome to clinically definitive MS (Hoffmann et al, 2010).…”
Section: B Cells and Antibodiesmentioning
confidence: 97%